Clonal deletion of self-reactive T cells in irradiation bone marrow chimeras and neonatally tolerant mice. Evidence for intercellular transfer of Mlsa (The Rockefeller University Press, 1989)
Tolerance to Mlsa has been shown to be associated with clonal deletion of cells carrying TCR beta chain variable regions V beta 6 or V beta 8.1 in mice possessing I-E antigens. To evaluate the rules of tolerance induction to Mlsa we prepared irradiation bone marrow chimeras expressing Mlsa or Mlsb and I-E by different cell types. Deletion of V beta 6+, Mlsa-reactive T cells required the presence of Mlsa and I-E products either on bone marrow-derived cells or on irradiated recipient cells. Tolerance was induced when Mlsa and I-E were expressed by distinct cells of the chimera. Also neonatally tolerized mice exhibited depletion of V beta 6+ cells after injection of I-E- Mlsa spleen cells (DBA/1) into newborn I-E+ Mlsb mice (BALB/c x B10.G)F1. These results suggest that the product of the Mlsa locus is soluble and/or may be transferred from cell to cell and bound to I-E antigens. The chimera experiments also showed that tolerance to Mlsa is H-2 allele independent, i.e., is apparently unrestricted. Differentiation of chimeric (H-2d/Mlsa x H-2q/Mlsb)F1 stem cells in either an H-2d or an H- 2q thymus revealed that tolerance assessed by absence of V beta 6+ T cells is not dependent on the thymically determined restriction specificity of T cells.